Degustando el recuerdo: comida, memoria, género y etnicidad en Amrik de Ana Miranda (Revista de Crítica Literaria Latinoamericana, 2015)
"Neuroscientific research and scholarly essays in the field of food studies have proven a strong bond between food and memory. This article shows how in Ana Miranda’s Amrik, food is a significant factor in the memories of the novel’s main character, and how food contributes to shape her identity. Therefore, taking as theoretical background studies on gastrocriticism I explore the relation among food, gender and ethnicity in the life of Lebanese inmigrants who arrived in Brazil at the end of the 19th century, historical backdrop of the novel. I argue that food representations allow to understand the characters’ sexual and social roles in the host country. Food is also a tool used to show how Lebanese inmigrants tried to keep their ethnicity once in Brazil."
Keywords: Ana Miranda; Amrik; Food studies; Gastrocriticism; Lebanese in Brazil